Rancang Bangun Alat Pendeteksi Uap Vaping dan Asap Rokok Berbasis Internet of Things Terintegerasi Aplikasi Android - Rifqi Fuadi Hasani; Benny Nixon; Alifa Humairah; Augita Yasmin (Politeknik Negeri Jakarta, 2023)
Smoking is one of causes disease which especially on respiratory tract because the cigarette were content that is not good for body. Passive smoker is really made a loss for smoke/vapor that they inhaled. So therefore, smoke detector was created by using connection of WiFi that connected to ESP32 which sending data of detection from MQ-2 sensor (detect content’s smoke of tobacco cigarette) and Adafruit sensor (detect content’s vapor of e-cigarette) to firebase that integrated by android software. This would faciliated for hotel firm because the hardware not only detect smoke of cigarette, but also vapor of vape will detected so guest that disobey the rules who using except cigarette will be fined which will be monitored by hotel’s employee remotely via android software. System of this hardware specifically only for once detected which if it detected, then green LED changed to yellow (e-cigarette) if the amount shows ≥ 25 ppm and/or red (tobacco cigarette) ) if the amount shows ≥ 0.05 ppm which followed by sound of buzzer and DC fan that will dispensed smoke/vapor out of room. Neutral room which was tested for 10 minutes produced a maximum of 0.03 ppm amount of detected smoke and 24 ppm amount of detected vapor. In the MQ-2 sensor experiment with a level of 1 burst it produces 0.42 ppm and delay of 2 seconds for the sensor to detect, in a room with a volume of 1050 m3 it returns clean with a delay of 11 seconds with amount of 0.04 ppm. In the Adafruit sensor experiment with a concentration of 1 burst it produces 33 ppm, a delay of 2 seconds for the sensor to detect, in a room with a volume of 1050 m3 it returns clean with a delay of 8 seconds with amount of 24 ppm.